6(y+1)=2(1-3y)-8

Simple and best practice solution for 6(y+1)=2(1-3y)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y+1)=2(1-3y)-8 equation:



6(y+1)=2(1-3y)-8
We move all terms to the left:
6(y+1)-(2(1-3y)-8)=0
We add all the numbers together, and all the variables
6(y+1)-(2(-3y+1)-8)=0
We multiply parentheses
6y-(2(-3y+1)-8)+6=0
We calculate terms in parentheses: -(2(-3y+1)-8), so:
2(-3y+1)-8
We multiply parentheses
-6y+2-8
We add all the numbers together, and all the variables
-6y-6
Back to the equation:
-(-6y-6)
We get rid of parentheses
6y+6y+6+6=0
We add all the numbers together, and all the variables
12y+12=0
We move all terms containing y to the left, all other terms to the right
12y=-12
y=-12/12
y=-1

See similar equations:

| -7x+12+4x=45 | | a2+2a=24 | | 8+8v=9v | | 12−5x+6x=4 | | -17.5y-4.75+18.6y=0.11+1.4y | | (20k+4)(33k-9)=360 | | 7k=5+2k | | 19g+17=20g | | -p+20+5=-15+4p | | -5q=-8-7q | | 3.01-7.5(2.3x-5.1432)=6.32x+5 | | 5y-9=-29 | | 6y+4=-20 | | 54=x*0,5x | | 17.2w+14.82=-15.87+13.9w | | 19+6y=19+13y | | 18c+20=20c | | 16b-13=3b+8b+17 | | -63=12x | | 6d(4d-5)=4d+12 | | 11x^2-13-7x=-7x+7x^2-12 | | 6u-10=10+10u | | 3.4m=7.82-3(8.7m-17.06) | | -4-2j=6-9j+2j | | 0x+6=1x+4 | | 5d-6=-2d+8 | | 2x+2x²=288 | | -7s=-8s+6 | | s/3=5;s=24 | | -10-9=-8y | | -6-8a=-8(a+4) | | 6x+11=10x+19 |

Equations solver categories